Morphological variation in Bessera (Asparagaceae: Brodiaeoideae) allows for the recognition of two new species - Gándara, Etelvina; Ortiz-Brunel, Juan Pablo; Castro-Castro, Arturo; Ruiz-Sanchez, Eduardo (Phytotaxa, 2021)
Bessera (Asparagaceae: Brodiaeoideae) is a genus endemic to Mexico. It currently has two described species: B. elegans with a wide geographic distribution from Durango and Sinaloa in the Sierra Madre Occidental, across the Transmexican Volcanic Belt to Oaxaca in the Sierra Madre del Sur, and B. tuitensis which is endemic to the Sierra del Cuale in Jalisco. Most of the morphological variation in Bessera occurs in western Mexico. We measured ten morphological characters for 280 plants from 21 populations, including B. tuitensis, to answer the following questions: Can Moore’s Group B of B. elegans be recognized as a different species? Are the newly included B. elegans s. l. populations from Colima different from B. elegans s. str., and from B. elegans s. l. (Moore’s group B)? Is there a significant relationship between morphological variation and climate variables for these species? The statistical analyses (ANOVA, MANOVA, and discriminant analysis) allowed us to recognize two new Bessera species, described here as B. elegantissima and B. ramirezii. Additionally, we provide a morphological key for Bessera, illustrations, a distribution map, and photographs of all the species.